TO EVALUATE THE COMPARATIVE EFFICACY OF SVALPAMASHA TAILA NASYA AND PARINATA KERIKSHEERADI NASYA IN AVABAHUKA (FROZEN SHOULDER) - Manjunath Akki*; Suresh N Hakkandi; Mohammed Lulu (AYUSHDHARA, 2019)
Avabahuka is a condition in which vitiated Vata lodges in Amsa Pradesha and by contracting leads to the Shosha of the muscles of the shoulder and upper arm. This disease disturbs the day to day activities of an individual and makes him dependent and very much depressed. Ayurveda has a great role to manage this disease successfully. Nasya Karma is one of the prime treatments of Avabahuka. It is especially indicated for the diseases of the parts in and above the shoulders. In Nasya Phalasruti it is mentioned that the skin, shoulders, neck, face, chest become well developed. So Nasya helps in developing strength of muscles in shoulder region. Objective of the study: To evaluate the efficacy of Svalpamasha taila Parinata keriksheeradi taila and comparative efficacy of Svalpamasha taila Nasya and Parinata Keriksheeradi Nasya in Avabahuka. Methods: 30 patients of Avabahuka, were randomly divided into two groups, Group A received Nasya Karma with Svalpamasha Taila for 14 days and the Group B received Nasya Karma with Parinata keriksheeradi taila nasya for 14 days. With help of assessment tools and gradation of symptoms, the findings of research work were statistically analyzed. Results: Results of this study shows that group A (Svaplamashataila) was more effective in reliving the symptoms of Avabahuka than Group B (Parinata keriksheeradi taila). So Group A is statistically significant than Group B.